The Effect of Telenursing-Based Five-Finger Hypnosis Therapy on Maternal Stress Among Mothers of Stunted Children: A Quasi-Experimental Study - Iwan Wahyudi; Tanti Suryawantie; Ishmah Hamidah (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Background: Stunting remains a major public health problem in developing countries, including Indonesia. In addition to nutritional factors, maternal psychological stress may indirectly affect caregiving quality and child well-being. Objective: This study aimed to examine the effect of telenursing-based five-finger hypnosis therapy on maternal stress levels among mothers of children with stunting. Methods: A quasi-experimental pretest-posttest control group design was conducted from March to May 2024 in Wanaraja Village, Garut Regency, Indonesia. A total of 34 mothers of children with stunting were recruited using purposive sampling and assigned to an intervention group (n = 17) and a control group (n = 17). The intervention group received telenursing-based five-finger hypnosis therapy for seven sessions over four weeks, while the control group received routine puskesmas services. Maternal stress was measured using 14 items derived from a modified DASS-42 questionnaire. Data were analyzed using the Friedman test and Mann-Whitney test. Results: Maternal stress in the intervention group decreased progressively from pretest to posttest 1 and posttest 2, with mean scores declining from 18.4 (SD 3.12) to 16.4 (SD 2.50) and 14.5 (SD 2.40), respectively. The control group also showed a slight reduction, from 18.9 (SD 2.29) to 17.9 (SD 2.77) and 17.6 (SD 2.50). However, the reduction in maternal stress was significantly greater in the intervention group than in the control group at week 2 (p = 0.036) and week 4 (p < 0.001), with a larger effect observed at week 4. Conclusion: Telenursing-based five-finger hypnosis therapy was associated with a greater reduction in maternal stress among mothers of children with stunting than routine care alone. This intervention may serve as a supportive psychosocial strategy in community-based stunting management programs.